Age at menarche and secular trend in Maharashtrian (Indian) girls - Bagga, Amrita; Kulkarni, Shaunak (Acta Biologica Szegediensis, 2000)
Age at menarche of 366 Maharashtrian Brahmin, Maratha and Scheduled Caste girls was studied and two hypotheses relating menarcheal age to physical growth were compared. Results indicated that both measurements, the height (the indicator of skeletal maturity), and the weight (the indicator of fat accumulation), were positively correlated with age at menarche. The well known phenomena of children achieving greater size and maturing earlier as manifested by menarche in girls and the secular trend in the age at menarche are well demonstrated in the present study on the Maharashtrian girls of Pune city. The lowering of age at menarche at an average rate of about 6 months per decade in the last three decades in the present study, as compared to 3-4 months in some countries of Europe, North America, and several parts of the world, reflects upon the now improved socio-economic, nutritional and general health conditions in India as compared to these countries where similar standards were achieved much earlier.